2013
DOI: 10.1155/2013/852368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Informal Care Time and Costs in Different Age-Related Dementias: A Review

Abstract: Objectives. Age-related dementia is a progressive degenerative brain syndrome whose prevalence increases with age. Dementias cause a substantial burden on society and on families who provide informal care. This study aims to review the relevant papers to compare informal care time and costs in different dementias. Methods. A bibliographic search was performed on an international medical literature database (MEDLINE). All studies which assessed the social economic burden of different dementias were selected. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 56 publications
2
21
1
Order By: Relevance
“…It has been reported that between 2005 and 2011 the cost of informal care for people with PD doubled ($5.4 million versus $11.2 million) [8]. This included income in a formal work environment foregone by carers [35]. The growth reflects the additional number of people with PD and higher average earnings in the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that between 2005 and 2011 the cost of informal care for people with PD doubled ($5.4 million versus $11.2 million) [8]. This included income in a formal work environment foregone by carers [35]. The growth reflects the additional number of people with PD and higher average earnings in the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the reviewed studies apply a societal perspective, the inclusion of different cost categories as well as cost components in direct costs vary. A lack of precise description, cost estimation and transparency in reviewed studies is evident and has been criticized earlier (Bloom et al, 2001;Wimo et al, 2011;Costa et al, 2013). A degree of consensus on the cost categories and cost components to be included in COI studies in dementia is required, especially against the background that dementia affects many different types of costs.…”
Section: Methodological Challenges and Recommendationsmentioning
confidence: 99%
“…19 We assessed informal care costs for caregivers who were not working or were over 65 years of age at 30% of the mean wage of employed caregivers. [20][21][22][23] Time spent on supervision was assumed to be zero cost for the same reasons why we assess it separately. 5,17,18,24 A maximum daily informal care time of 16 hours was assumed in order to allow for other activities and sleeping time.…”
Section: Key Pointsmentioning
confidence: 99%